LAS ESPECIES ARGENTINAS DEL GENERO COELIOXYS (iCYRTOCOELIOXYS) (HYMENOPTERA: MEGACHILIDAE) - Toro, Haroldo; Fritz, Manfredo (Acta Entomológica Chilena, 2022)
The argéntinian species of Coelioxys (Cyrtocoelioxys) sensu Mitchell 1973 are studied. The following species are added to the list given by Mitchell: C. missionun Holmberg, C. pedregalensis Holmberg, C. subtropicales Holmberg and C. rugulosa Friese. The type species of C. humahuakae Holmberg, C. macaría Holmberg and C. quaerens erythronotos Schrottky could not be found. The following new species are described andfigured: C. alisal, C. balasto. C. saltensis. C. tastil and C. trancas. A key for the argentinian species oí Cyrtocoelioxys is given.